A tale of two Martins: Is Luther to blame for Heidegger's destruction of ontotheology?. Issue 3 (2nd November 2022) - Bielfeldt, Dennis
Abstract: Much has been written about Heidegger's indebtedness to Luther in developing Being and Time . Recently Duane Armitage has claimed that since Heidegger is the "root to all continental philosophy of religion and postmodern theology, " and since his "disdain for onto‐theology is rooted in Luther, . . . essentially all postmodern theological thinking is fundamentally Lutheran." Clearly, both Martins de‐emphasize theology's penchant for abstract metaphysics and look instead to recover the facticity of concrete lived Christian existence. But surface similarities should not occlude what profoundly differentiates the two, for the Martins depart radically in what they thought thinking did and what the truth‐conditions of their respective discourses were. Luther who assumed theological realism was concerned with how human beings really stand in relation to God, while Heidegger brackets such questions in favor of a description of the phenomenological shape of the Christian life. I employ elementary model theory in order to provide greater precision and accuracy in evaluating the stark semantic differences between their respective approaches.